Testing statcom model in IEEE power system network using PSCAD software - Mohd Firdaus, Daud (2008)
In any transmission system, the ultimate goals are to transmit power with high quality, economical and low risk of system failure. The ever increasing of power demands and loads especially non-linear loads making the power system network become complex to operate and the system becomes insecure with large power flows without adequate control. One way to introduce power system control is by applying controller known as FACTS (Flexible AC Transmission System) controllers. STATCOM (Static Synchronous Compensator) is one of the FACTS controllers and can be introduced to the power system to regulate terminal voltage and to improve system’s stability. By using IEEE 4 bus power system network, the effectiveness of STATCOM is tested by applying the controller at the critical location of the power system. The critical location of a power system is determined by the voltage drop that falls below 0.95 or above 1.05. Using PSCAD/EMTDC simulation software, the simulations of STATCOM in IEEE 4 bus power system networks can be realized. To verify the PSCAD/EMTDC simulation results, load flow analysis are acquired using MATLAB software through Hadi Saadat’s load flow analysis method. With these softwares, both systems’ power flow can be compared to determine the effectiveness of STATCOM in the power transmission system.